Utilization of google sites as a web-based digital marketing platform web-based digital marketing platform for MSMEs as an innovative solution to improve competitiveness competitiveness in the digital era - Zalukhu, Hadirat Berkat; Zalukhu, Try Sepakat; Zega, Firdaus Sibohou; Lase, Four Steven (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic development, particularly in urban areas like Banjarmasin. However, their ability to compete in the digital era remains limited due to low adoption of digital marketing strategies. This study aims to examine the potential use of Google Sites as a user-friendly, accessible, and cost-effective web-based digital marketing platform for MSMEs in Banjarmasin. Prior studies have shown that the lack of technical skills and digital literacy are major barriers for MSMEs in leveraging more complex technologies. Google Sites, as part of the Google Workspace ecosystem, offers simplified tools for website creation that can address these barriers. Method: This research employed a descriptive qualitative approach through literature review. Data was collected from previous studies, government reports, and Google’s official documentation to analyze the suitability of Google Sites features for MSME digital marketing needs. Findings: The findings indicate that Google Sites provides essential functionalities—such as customizable templates, media integration, mobile responsiveness, and analytics support—that can significantly enhance MSMEs' online visibility and consumer engagement. These features align with the theoretical expectations regarding the adoption of low-barrier digital tools in small-scale enterprises. Conclusion: In conclusion, Google Sites is a feasible and innovative solution for improving the competitiveness of MSMEs in the digital economy. This study offers a contextual analysis of Google Sites specifically for MSMEs in Banjarmasin, which has not been explored extensively in prior literature. Novelty/Oriignality of this Article: The novelty of this study lies in providing a focused evaluation of Google Sites as a digital marketing tool tailored to the specific challenges of MSMEs in Banjarmasin. Unlike prior research, it connects technical platform features with local business needs using a literature-based, non-interventionist approach.